Others Had Similar Problems and You Were Not Alone - Arndt, M.; Murchie, F.; Schembri, A.; Davidson, Patricia (Lippincott Williams and Wilkins, 2009)
Background: Dealing with psychological and social issues is an important aspect of comprehensive cardiac rehabilitation (CR) programs. Study Aim: This study aims to evaluate the use of an open-group mutual aid model facilitated by a social worker and occupational therapist in a secondary prevention CR program. Method: A mixed-method study, using questionnaires, focus group data, and reflective interviews of group facilitators, was used to evaluate the program. Study findings: Key themes emerging from this study were (1) the need for provision of hope; (2) a desire for structure and support; (3) appreciation of support of fellow group participants; and (4) the need to individuals to review, process, and interpret their illness trajectory. Conclusions: In this single site study, an open-group model using a mutual aid model was acceptable and helpful as a method to facilitate adjustment after an acute cardiac event. Further evaluation of this approach using experimental methods is warranted.